(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Cryptography serves as a fundamental process for safeguarding information, enabling exclusive access and comprehension by intended users while thwarting unauthorized intrusion. Its origins trace back to 2000 BC, employing rudimentary methods to obscure information, decipherable solely by designated recipients. As technology progressed, more intricate techniques were devised to fortify data against breaches. Sophisticated mathematical algorithms like AES and RSA emerged for data encryption and decryption. Notably, cryptography has found recent prominence in computer science, particularly in the realm of cryptographic currencies or cryptocurrencies. The advent of blockchain technology, a distributed ledger system underpinning cryptocurrencies like Bitcoin, has brought forth an elevated level of cryptographic implementation. Public-key cryptography, Hash Functions, Merkle Trees, and advanced digital signatures, including Elliptic Curve Digital Signatures, constitute the core of blockchain’s cryptographic arsenal. This intricate cryptographic framework fortifies the security and seamless transmission of data within the blockchain domain, contributing to its burgeoning popularity. Blockchain seamlessly integrates cryptography at various stages, leveraging sophisticated cryptographic techniques borrowed from the realm of cryptography. This paper aims to introduce cryptography and blockchain technology, shedding light on their integration to offer optimal data security. A comprehensive review of cryptographic attacks within the blockchain context is provided, alongside an examination of the diverse security services inherent to blockchain.